Allelopathic activity of Dendrophthoe pentandra as a potential bioherbicide to inhibit seed germination and seedling growth of Eleusine indica - Lutfan Alharits; Niarsi Merry Hemelda; Yasman; Windri Handayani (Nusantara Bioscience, 2020)
Abstract. Alharits L, Hemelda NM, Yasman, Handayani W. 2020. Allelopathic activity of Dendrophthoe pentandra as a potential bioherbicide to inhibit seed germination and seedling growth of Eleusine indica. Nusantara Bioscience 12: 33-39. Dendrophthoe pentandra (L.) Miq. is a common parasitic plant in Southeast Asia. As a parasitic plant, it exhibits phytochemicals important for infecting its host, which may be potential as bioherbicide. This study was aimed to evaluate allelopathic activity of D. pentandra (stem and leaf extracts) to control Eleusine indica (L.) Gaertn. seed germination and growth. Methanolic extracts of D. pentandra stem and leaf (0, 1, 2, 3, 4 and 5 mg/mL in water) were treated on E. indica seeds in a petri dish for 10 days. After 10 days, germination of treated E. indica seeds was significantly reduced and reached >80% inhibition at 5 mg/mL. Moreover, E. indica roots were more sensitive compared to E. indica shoots, indicated by root inhibition >50% at 1 mg/mL and reached >90% inhibition at 5 mg/mL. Leaf extract presented stronger inhibition than stem extract, but not significant. It may be related to the higher accumulation of phenolic and flavonoid compounds in leaf extract than in stem extract. This is the first report of allelopathic activity in D. pentandra to inhibit E. indica germination and growth. Therefore, further study in a greenhouse, as well as metabolism effects of D. pentandra on the target weeds are important to provide comprehensive evaluation of D. pentandra potential as bioherbicide.